2016
DOI: 10.1099/jmm.0.000208
|View full text |Cite
|
Sign up to set email alerts
|

Genotype analysis of varicella-zoster virus isolates from suburban Shanghai Municipal Province, China

Abstract: We also observed significant inter-strain variations. Received 1 December 2014Accepted 8 December 2015 INTRODUCTIONThe genome of the varicella-zoster virus (VZV), a member of the family Herpesviridae and subfamily Alphaherpesvirinae, has been fully sequenced and found to consist of 125 kb of linear, dsDNA coding for 71 ORFs. VZV is the causative agent of varicella and herpes zoster (HZ) infections in humans. As a primary infection, varicella usually occurs in childhood, although it can be reactivated and manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…In the present study, one genotype J VZV strain was detected from 26 samples with anti-VZV IgM positive. Similar to the present findings, Sun et al identified the 69 VZV strains from clinical patients between May 2011 and June 2013 in eastern China as genotype J [29]. Therefore, our results and previous findings suggested that the current varicella vaccine is suitable for regular use in China because the vaccine strain (Oka strain) belongs to genotype J.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, one genotype J VZV strain was detected from 26 samples with anti-VZV IgM positive. Similar to the present findings, Sun et al identified the 69 VZV strains from clinical patients between May 2011 and June 2013 in eastern China as genotype J [29]. Therefore, our results and previous findings suggested that the current varicella vaccine is suitable for regular use in China because the vaccine strain (Oka strain) belongs to genotype J.…”
Section: Discussionsupporting
confidence: 91%
“…These results were consistent with previous observations (17). However, it was slightly different from the predominant genotype in suburban Shanghai in previous report (18).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present findings, Sun et al identified the 69 VZV strains isolated from clinical patients between May 2011 and June 2013 in eastern China as genotype J [30].…”
Section: Discussionsupporting
confidence: 90%